Batik Socialization for Tourists at Yogyakarta Batik Museum - Endah Nurhawaeny; Muhammad; Fitri Alfiani; An Nuur Khairune Nisa (Ann Publisher, 2024)
Batik is a symbol of Indonesian clothing. Different Vedic batik motifs are spread throughout Indonesia. One of them is the Yogyakarta batik motif. Yogyakarta is the second tourist destination after Bali, so tourists who are present at all times are in Yogyakarta. Some tourists are interested in knowing how to make Yogyakarta batik motifs. Batik Museum of Yogyakarta was built by the initiation of marriage couples Hadi Nugroho and Dewi Sukaningsing to conserve the batik collection and to make process supporting equipment. Its collection is about 1200, including batik fabric, batik tools, and equipment like pans, anglo, canting, and other supporting equipment. This community service activity is a promotional step to preserve Indonesian batik by doing batik activities at the Yogyakarta batik museum. The activity was attended by tourists who visited Yogyakarta and were interested in experimenting with batik.